2010
DOI: 10.1159/000319743
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumothorax During Chemotherapy: A Case Report

Abstract: Background: Spontaneous pneumothorax (SP) associated with malignant disease is relatively infrequent but has important diagnostic and therapeutic implications. Case Report: We describe a case of SP that occurred during chemotherapy with ifosfamide and doxorubicin in a patient with an advanced pleomorphic sarcoma. The pneumothorax developed secondary to the rapid regression of peripheral pulmonary metastases presumably resulting in bronchopleural fistula formation. After treatment with chest tube drainage, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Several previous reports showed that the histologic types of primary lung malignant disease complicated by pneumothorax include adenocarcinoma, squamous cell carcinoma, large call carcinoma, and sarcoma [4, 7, 13–15]. However, the number of case reports of patients with pulmonary pleomorphic carcinoma increased after the disease was formally placed in the WHO histologic classification, and reports of the tendency of this disease toward necrosis and chest wall invasion are known to be more frequent [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports showed that the histologic types of primary lung malignant disease complicated by pneumothorax include adenocarcinoma, squamous cell carcinoma, large call carcinoma, and sarcoma [4, 7, 13–15]. However, the number of case reports of patients with pulmonary pleomorphic carcinoma increased after the disease was formally placed in the WHO histologic classification, and reports of the tendency of this disease toward necrosis and chest wall invasion are known to be more frequent [16].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid regression of tumors following chemotherapy has been thought to be one of the possible causes of spontaneous pneumothorax post-chemotherapy [ 5 , 6 ]. Spontaneous pneumothoraces occur more often in metastatic osteogenic sarcomas, germ cell tumors, and lymphomas [ 7 , 8 ]. Male breast cancer is uncommon, and presentation with bilateral secondary spontaneous pneumothorax is rare.…”
Section: Introductionmentioning
confidence: 99%